2017
DOI: 10.4300/jgme-d-17-00116.1
|View full text |Cite
|
Sign up to set email alerts
|

Aligning In-Service Training Examinations in Plastic Surgery and Orthopaedic Surgery With Competency-Based Education

Abstract: Background In-service training examinations (ITEs) are used to assess residents across specialties. However, it is not clear how they are integrated with the Accreditation Council for Graduate Medical Education Milestones and competencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…7 Of the Accreditation Council for Graduate Medical Education core competencies, OITE questions focus primarily on patient care and medical knowledge. 8 In addition to performance during residency training, multiple studies have shown the OITE to be a significant predictor of the American Board of Orthopaedic Surgery (ABOS) part I performance. [9][10][11] In a study evaluating 3,132 ABOS part I examinees, Swanson et al found the OITE to be a good predictor of ABOS score and pass-fail outcome.…”
Section: Importance Of the Orthopaedic In-training Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Of the Accreditation Council for Graduate Medical Education core competencies, OITE questions focus primarily on patient care and medical knowledge. 8 In addition to performance during residency training, multiple studies have shown the OITE to be a significant predictor of the American Board of Orthopaedic Surgery (ABOS) part I performance. [9][10][11] In a study evaluating 3,132 ABOS part I examinees, Swanson et al found the OITE to be a good predictor of ABOS score and pass-fail outcome.…”
Section: Importance Of the Orthopaedic In-training Examinationmentioning
confidence: 99%
“…7 Of the Accreditation Council for Graduate Medical Education core competencies, OITE questions focus primarily on patient care and medical knowledge. 8…”
Section: Importance Of the Orthopaedic In-training Examinationmentioning
confidence: 99%